Inovasi Penilaian Berbasis Teknologi dalam Pendidikan Agama Kristen - Hutapea, Rinto Hasiholan (Shift Key : Jurnal Teologi dan Pelayanan, 2024)
This study aims to examine the role of Christian Religious Education teachers in utilizing innovative learning outcomes assessment in the digital era. In the context of education that is increasingly dependent on technology, teachers are required to have adequate digital competencies. The research method is a qualitative study with a literature study approach. The results show that although there are significant challenges in the use of learning technology, technology also provides various benefits in the assessment of learning outcomes. Technology-based assessment enables more flexible measurement of competencies and makes it easier for teachers to provide quick feedback. This research confirms the importance of developing teachers' digital competencies in creating competitive learning in the digital era.